Vulvar Pain : From Childhood to Old Age - Graziottin, Alessandra; Murina, Filippo (Springer International Publishing : Imprint: Springer, 2017)
This book offers detailed coverage of all aspects of vulvar pain in age groups from children to the elderly, with a particular focus on factors that precipitate or maintain the pain. Guidance is provided on diagnosis and treatment, and careful consideration is given to special circumstances associated with vulvar pain, including childbirth, recurrent cystitis, female genital mutilation, medical comorbidities, and sexual comorbidities in both partners. Vulvar pain of neurogenic and iatrogenic origin is also fully discussed. Two innovative chapters present case reports highly relevant to clinical practice and address outstanding issues, including controversies and difficulties in terminology, initial triggers, the role of stress, psychogenic causes, and misuse and abuse. The book is exceptional in covering vulvar pain throughout the human life span and in a wide range of situations, and it will be of value to all who are involved in management of the condition.